PSIKOEDUKASI STRATEGI MENGELOLA KELAS BAGI GURU DI SEKOLAH DASAR (Jurnal Bakti Masyarakat Indonesia, 2019)
Teachers need information to understand the characteristics of students, especially in the meanings of individual differences. Community service is intended to answer the problems perceived by the teacher. Based on the information obtained, then formulated the core problems experienced by teachers in the form of the need for knowledge and understanding the characteristics of students of public primary schools in Jakarta. Teachers need information about classroom managing techniques. The aimed of this activity was to improve the knowledge and understanding of teachers through psychoeducation with providing life skills intervention. The subjects or participants in this activity are teachers. A pre-test was first conducted that measured teachers' perceptions of how to manage the class by using Teacher's Sense of Efficacy Scale (TSES) questionnaire. After that, the resource person provides material on classroom management. Data analysis was using SPSS 18 version for windows. The paired sample T-test technique was used to see the effectiveness of the psychoeducation. There was no difference between a score of the pre-test (M = 4.0190, SD = 0.51470) and a score on the post-test (M = 4.1238, SD = 0.52867); Z = -0.788, and p = 0.431> 0.05. However, in the reflection of the activities of each participant expressed the usefulness of this event. Based on the activities that have been done, it can be concluded that the teachers who have provided feedback through self-report evaluation results, states that the students get the benefits of these activities.